Group Analysis of FMRI and NIR Data Simultaneously Acquired During Visual Stimulation in Humans - Toronov, Vladislav Y. (2006)
We use our new combined functional near infrared spectro-imaging (fNIRSI) and magnetic resonance imaging (MRJ) technique to compare fMRI and fNIRSI data at different activation conditions, to obtain new information about the underlying physiology of the blood oxygen level dependent (BOLD) signal used in fMRI, and to assess statistical characteristics of spatial functional information provided by the group analysis of fNIRSI data. To achieve these goals we have acquired simultaneously fNIRSI and fMRI data during the presentation of the checkerboard reversing with different frequencies, and analyzed these data following the standard correlation and group analysis of variance pathway used in functional neuroimaging. . We have found that while the time courses of oxy-, deoxy-, and total- hemoglobin responses are equally well correlated with the time course of the BOLD response, the spatial pattern and magnitude of the BOLD response is better related to those of the oxy-, and total- hemoglobin responses rather than to the deoxyhemoglobin response. The statistical significance of the fNIRSI group maps is inferior to that of fMRI, and can be particularly compromised by the anatomical features of subjects.